Predictive goal coding by dentate gyrus somatostatin-expressing interneurons in male mice - Mei Yuan; Aurore Cazala; Sven Goedeke; Christian Leibold; Jonas-Frederic Sauer; Marlene Bartos (Nature Communications, 2025)
Abstract To select appropriate behaviour, individuals must rely on encoding of relevant features within their environment in the context of current and past experiences. This function has been linked to goal-associated activity patterns of hippocampal principal cells. Using single-unit recordings from optogenetically identified somatostatin-expressing interneurons (SOMIs) in the dentate gyrus of head-fixed mice trained in a spatial goal-oriented reward-learning task in virtual realities, we show that SOMI activity temporally precedes reward-locations in expert mice characterized by goal-anticipatory behaviour. Predictive goal-encoding by SOMIs is lost after translocation of learned goals to novel previously unrewarded sites leading to rapid reductions in anticipatory behaviour and fast reconfiguration of SOMI activity to times after reward onset in association with reward consumption at novel goal-sites. Chemogenetic silencing of SOMIs caused a loss of memory that trained goal-sites were no longer available. Thus, our data reveal the ability of SOMIs to flexibly encode goal-locations depending on current and past experiences to bias behavioral outcomes.